2003
DOI: 10.1111/1469-7610.00143
|View full text |Cite
|
Sign up to set email alerts
|

Pitch memory, labelling and disembedding in autism

Abstract: Background:  Autistic musical savants invariably possess absolute pitch ability and are able to disembed individual musical tones from chords. Enhanced pitch discrimination and memory has been found in non‐savant individuals with autism who also show superior performance on visual disembedding tasks. These experiments investigate the extent that enhanced disembedding ability will be found within the musical domain in autism. Method:  High‐functioning children with autism, together with age‐ and intelligence‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(204 citation statements)
references
References 37 publications
11
187
2
4
Order By: Relevance
“…A closer look at the literature, however, reveals that surprisingly few studies actually estimated pitch discrimination thresholds for pure tones in ASD. The majority of studies investigated more advanced pitch processing aspects like categorization, labelling, memory or disembedding, and they often used much more complex auditory stimuli or speech stimuli (e.g., Foxton et al 2003;Heaton 2003;Heaton et al 2005Heaton et al , 2008bJärvinen-Pasley and Heaton 2007;Järvinen-Pasley et al 2008a, b;Mottron et al 2000). Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at the literature, however, reveals that surprisingly few studies actually estimated pitch discrimination thresholds for pure tones in ASD. The majority of studies investigated more advanced pitch processing aspects like categorization, labelling, memory or disembedding, and they often used much more complex auditory stimuli or speech stimuli (e.g., Foxton et al 2003;Heaton 2003;Heaton et al 2005Heaton et al , 2008bJärvinen-Pasley and Heaton 2007;Järvinen-Pasley et al 2008a, b;Mottron et al 2000). Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had already found enhanced simple lowlevel visual processing (O'Riordan et al 2001;Plaisted et al 1998) and spared (Spencer et al 2000;Blake et al 2003) or diminished complex low-level visual processing (Milne et al 2002). In the auditory domain, enhanced simple low-level processing had been reported for pitch discrimination and chord disembedding (Bonnel et al 2003;Heaton 2003), in which perceptual performance depends on spectral processing. Using a complex low-level auditory task, Alcantara also found diminished temporal but intact spectral processing in children with autism (Alcantara et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The EPF model predicts that A1-mediated perceptual processing will be superior in autism. Indeed, superior low-order auditory perception has been reported in experimental paradigms involving pitch perception (Bonnel et al 2003) and chord segmentation (Heaton 2003). However, few studies assessing complex low-level perceptual tasks in the auditory domain that require extensive neural integration have yet been conducted (Teder-Salejarvi et al 2005;Alcantara et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Music therapy as an alternative medicine in conjunction with the effect of joint attention, social interaction and verbal/nonverbal communication, can address motor dysfunction, sensory deficits and behavioral problems in children with autism [15]. The rhythm of music, which is the most structural part of it, can influence some different areas of the brain such as the motor area by making auditory motor integration and coordination [16][17][18].…”
Section: Introductionmentioning
confidence: 99%